2014
DOI: 10.3389/fnbeh.2014.00260
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sertraline administration from adolescence to adulthood on physiological and emotional development in prenatally stressed rats of both sexes

Abstract: Sertraline (SERT) is a clinically effective Selective Serotonin Reuptake Inhibitor (SSRI) known to increase and stabilize serotonin levels. This neurotransmitter plays an important role in adolescent brain development in both rodents and humans, and its dysregulation has been correlated with deficits in behavior and emotional regulation. Since prenatal stress may disturb serotoninergic homeostasis, the aim of this study was to examine the long-lasting effects of exposure to SERT throughout adolescence on behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 108 publications
(169 reference statements)
2
20
0
Order By: Relevance
“…However, we found no differences in the locomotor activity as effect of SERT administration. This supports previous results [13] [51] [54] in which fluoxetine or SERT reduced the stressinduced immobility, without influencing other activities.…”
Section: The Effects Of Sertralinesupporting
confidence: 93%
See 2 more Smart Citations
“…However, we found no differences in the locomotor activity as effect of SERT administration. This supports previous results [13] [51] [54] in which fluoxetine or SERT reduced the stressinduced immobility, without influencing other activities.…”
Section: The Effects Of Sertralinesupporting
confidence: 93%
“…Only offspring from litters containing 9 -12 pups were used in the present experiments. Offspring were weaned at 21 days of age and were separated into group cages housing four animals of the same sex and treatment as previously described [13]. No differences in litter sizes, in the male-to-female ratio of the offspring or inpre-weaning-mortality were found.…”
Section: Prenatal Stress Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, exposure to both prenatal SSRIs and maternal depression can increase internalizing behaviors (depression, anxiety, and withdrawal) in 3 and 4 year olds (Oberlander et al, ). Preclinical studies have also demonstrated that developmental SSRI exposure can have long term effect on affective‐like behaviors in offspring with a well‐documented increase in both anxiety‐ and depression‐related behaviors, particularly in adult male offspring, after prenatal or early postnatal treatment with SSRIs (Ansorge, Zhou, Lira, Hen, & Gingrich, ; Karpova, Lindholm, Pruunsild, Timmusk, & Castren, ; Lisboa, Oliveira, Costa, Venancio, & Moreira, ; Noorlander et al, ; Olivier et al, ; Popa, Lena, Alexandre, & Adrien, ; Smit‐Rigter et al, ), however, this is not always the case and often minimal long‐term effects of perinatal SSRI exposure has been reported (Nagano, Liu, Inagaki, Kawada, & Suzuki, ; Pereira‐Figueiredo, Sancho, Carro, Castellano, & Lopez, ). It should be noted that the majority of these studies did not investigate the effect of perinatal SSRI exposure using a model of maternal depression.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous reports (Pereira-Figueiredo et al, 2014, 2015), SERT was given orally (Besitran© Pfizer S.A. Madrid, Spain) at a dose of 5.0 mg/kg/day. Using calibrated bottles, which were monitored every 2 days, liquid consumption was controlled, and the dose of the drug was adjusted on the basis of the liquid consumed and mean body weight.…”
Section: Methodsmentioning
confidence: 99%